Developing nutrition knowledge and attitude measures for athletes with the knowledge-attitude-behavior model - Teo, C. J. H.; Burns, S. F.; Kawabata, M. (Research Quarterly for Exercise and Sport, 2023)
Purpose: Nutrition education programmes are often created to improve dietary intake in athletes. Unfortunately, the inconsistent link between nutrition knowledge and dietary behavior suggests that nutrition knowledge may not be a key influencer of dietary behavior. The Knowledge-Attitude-Behavior (KAB) model has been used in nutrition education although studies that evaluated this model were largely compromised by poorly constructed instruments and methodological discrepancies. Method: To improve understanding of the model, a Nutrition Knowledge Questionnaire (NKQ) and Athlete`s Perspective on Nutrition (APN) instrument was developed using the theory of planned behavior as its theoretical framework. Validity and reliability were examined for 193 Sports Science students and 11 elite netballers. Content and face validity of the 48-item NKQ was confirmed by expert sport dietitians. Discriminant validity of the NKQ and factorial validity of the APN was established. Both instruments demonstrated acceptable internal consistency and good test-retest reliability. The final instruments were administered to elite athletes in a pilot study to understand the KAB model. Results: Correlation between nutrition knowledge and dietary behavior was significant (r = .811, p = .01). Nutrition knowledge was a positive predictor of netballers` dietary behavior (ß = .8, t(2) = 3.899, p = .005) but attitude was not (ß = -.097, t(2) = -.471, p = .65). Conclusion: Two psychometrically sound instruments developed in this study can be used to measure nutrition knowledge and attitude in an Asian group of athletes. The pilot study with athletes showed that nutrition knowledge predicted dietary behavior.